Selective Sphingosine 1-Phosphate Receptor 1 Modulation Augments Thrombolysis of Low-Dose Tissue Plasminogen Activator Following Cerebrovascular Thrombosis - Li, Han-Dong; Li, Ran; Kong, Ying; Zhang, Wenyan; Qi, Caiyun; Wang, Dan; Hao, Hongying; Liu, Qiang (Frontiers in Immunology, 2022)
Background Results from our recent study demonstrate that sphingosine-1-phosphate receptor 1 (S1PR1) modulation improves microvascular hemodynamics after cerebrovascular thrombosis. This study was to determine the microvascular hemodynamic effects of a sub-thrombolytic dose of tPA combined with a selective S1PR1 modulator ozanimod in a mouse model of cerebrovascular thrombosis. Methods Microvascular circulation in mice was monitored in vivo by two-photon microscopy. Thrombosis was induced in cortical arterioles by laser irradiation. Arteriolar flow velocity was measured by line-scanning following plasma-labeling with fluorescein-dextran. Results Laser‐induced thrombosis led to a persistent reduction of flow velocity in cortical arterioles. Sub-thrombolytic dose of tPA along with vehicle control did not improve the flow velocity in cortical arterioles following thrombosis. In contrast, a sub-thrombolytic dose of tPA along with ozanimod dramatically restored flow velocity in cortical arterioles following thrombosis. Ozanimod did not affect coagulation and bleeding time. Notably, ozanimod reduced thrombus volume without altering microvascular lumen diameter. In addition, ozanimod reduced leukocyte components within the thrombus. Conclusions These findings demonstrate that the thrombolytic effect of a sub-thrombolytic dose of tPA is markedly enhanced by S1PR1 modulation, implying that S1PR1 modulation may improve the therapeutic benefit of low-dose tPA in patients with acute ischemic stroke.